Maldives : 2001 Article IV Consultation-Staff Report; and Statement by the Executive Director for Maldives. (IMF Staff Country Reports; Country Report, 2019)
This 2001 Article IV Consultation with Maldives highlights that the economic challenges faced by Maldives are strongly influenced by geography and environment. The government's overarching development strategy consists of creating new growth centers in the north and the south of the country and massive land reclamation in the vicinity of Male. Notwithstanding a slowdown in growth in 2000, Maldives' economy has prospered with the rapid expansion of tourism and the modernization of the fisheries. At the conclusion of the last Article IV consultation on November 9, 2000, Executive Directors praised Maldives' overall performance, however, warned of emerging imbalances. Fiscal slippage, compounded by adverse external developments, has been the main cause of recent imbalances in the Maldivian economy, manifested in rapid monetary expansion and sustained pressure on the exchange rate. The report shows that monetary developments have been dominated by central bank financing of fiscal deficits and excess demand for foreign exchange. The IMF staff team concluded that an adjustment of the exchange rate was not warranted until other options had been explored more fully.